HUBUNGAN LITERASI ARTIFICIAL INTELLIGENCE DAN SELF-REGULATED LEARNING MAHASISWA DALAM PENYUSUNAN SKRIPSI - Pebrianti, Sintia; Wulandari, Heni; Rahmat, Dadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the relationship between AI literacy and self-regulated learning among regular students of FKIP UMMI who were writing their undergraduate theses. This study employed a quantitative correlational research design. The participant consisted of 100 regular FKIP students who were writing their undergraduate theses and were selected using purposive sampling with proportional alocation. Data were collected through AI literacy and self-regulated learning questionnaires that had undergone validity and reliability testing. Data were analyzed using descriptive statistics and inferential statistics including normality, linearity and Pearson Product-Moment correlation test with the assistance of SPSS Statistic 27. The finding revealed a positive and statistically significant relationship between AI literacy and self regulated learning (r = 0,664; p < 0,001). The correlation was categorized as strong, indicating that student with high AI literacy tended to demonstrate higher levels of self-regulated learning during the theses-writing process. In conclusion, AI literacy is positively associated with self-regulated learning among undergraduate students writing their theses. These findings suggest that promoting AI literacy, particularly the ability to understand, evaluate and use AI responsibly may contribute to strengthening students’ self regulated learning in academic contexts.